21st Century Learning Model Integrated to 6C to Increase Students’ Engagement in English Subject: Lesson Study based Classroom Action Research - Rizkariani Sulaiman; Umar Mansyur (Jurnal Sinestesia, 2023)
Students at school need to be equipped with 21st century life skills so that they have the skills to face and overcome life's challenges and demands. Therefore, a 21st century skills-based learning model is needed which is obtained through analyzing student needs. The aim of this research is to find out 21st century learning models that are applicable to English language learning for class VII junior high school students. The type of research is Classroom Action Research based on Lesson Study with a qualitative descriptive approach. The research subjects were students in class VII-8 consisting of 34 (thirty four) students. The research instrument used was an observation sheet consisting of observing the implementation of lesson study, observing learning activities, observing student involvement in each cycle; interviews in the form of open ended questions to strengthen findings during observation and documentation. From the average value per session, it shows that the highest value for teacher activities was in cycle 2 of learning Models 2 and 3 with the same average value, namely 3.9; next cycle 1 Model 3 is 3.89; cycle 1 Model 2 with an average value of 3.86; then cycle 2 Model 1 which is 3.7 and finally cycle 1 Model 1 which is 3.66. In the aspect of student behavioral involvement with the application of learning models 1, 2 and 3 it is included in the very good category but the highest student behavioral involvement is in Cycle 2 Method 3 ( application of the Project based Learning model) which reached 95.6. In the aspect of emotional involvement, there are differences in the criteria for student involvement in the application of learning models 1, 2 and 3. In the application of model 1 (Discovery Learning) it is in good criteria with an average score of 73.5 in Cycle 1 and 75 in cycle 2. Meanwhile, students' emotional involvement is in the very good category in the application of learning models 2 and 3 and achieved the highest average score in Cycle 2 of the application of Method 3, namely 93.5. Student involvement increases in learning activities that combine providing interesting apperception, presenting problems that can be solved (problems are not too difficult and not too easy), completing projects that train creativity, performance and technological adaptation.